The clinical utility of sonographic cervical length in the management of preterm parturition at 28–32 weeks of gestation. (2nd November 2015) - Benshalom-Tirosh, Neta; Tirosh, Dan; Aricha-Tamir, Barak; Weintraub, Adi Y.; Erez, Offer; Mazor, Moshe; Hershkovitz, Reli
Abstract: Objectives : The aim of this study was to evaluate the role of cervical length measurement in early third trimester (28–32 weeks) as a predictor of preterm delivery (PTD), in women presenting with preterm parturition. Methods : Cervical length was measured prospectively, in singleton pregnancies at 28–32 weeks with preterm contractions (PTC). A multivariate linear regression model was performed to assess the association between cervical length and gestational age at delivery. Logistic regression analysis with PTD before 34 and 37 weeks of gestation as the outcome variable was performed to control for confounders. Results : Fifty-six women were included, mean gestational week at presentation and at delivery were 29.88 ± 1.13 and 37.05 ± 2.86, respectively. There was a direct association between short cervical length at admission and gestational week at delivery ( p =  0.027). This association remained significant even after controlling for confounders. Short cervical length was significantly associated with PTD before 34 ( p =  0.045) or 37 ( p =  0.046) weeks of gestation. Conclusions : Third trimester cervical length measurement in patients with PTC is associated with gestational week at delivery, as well as PTD prior to 34 and 37 weeks of gestation. Therefore, examining cervical length is clinically valuable and probably cost-effective during early third trimester.